Henry David Thoreau and Self-Determination of Personality - Pavilionis, Rolandas (Problemos, 1973)
An attempt is made in the paper to reconstruct in its essential features the intellectual portrait of the 19th century philosopher and writer Henry David Thoreau, the eminent representative of the American school of transcendentalism. Against the background of spiritual actualities of the modem American society torn by internal contradictions, it seeks to evaluate the significance of the ideas proclaimed in his works and manifested by his very way of life. The author tries to disclose the philosopher’s concept of human existence, which the latter does not reduce to the accumulation of material wealth but denies the disproportion between man’s intellectual and technological progress and which consists in the development of his natural and spiritual potential. Thoreau’s moral philosophy, asocial as it is, unlike many contemporary bourgeois theories, does not present a variation of the philosophy oil renunciation. On the contrary, it is a kind of philosophy deeply concerned with waking up those in spiritual drowsiness, the philosophy of creative individuality striving to cognize the nature surrounding him and contained in his very self.